2022
DOI: 10.1186/s12885-021-09028-4
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of PD-1 inhibitor after initial failure of PD-L1 inhibitor in Relapsed/Refractory classical Hodgkin Lymphoma

Abstract: Purpose We sought to understand the clinical course and molecular phenotype of patients who showed disease progression after programmed cell death ligand 1 (PD-L1) inhibitor treatment but subsequently responded to PD-1 inhibitor treatment. We also explored the response to PD-1-axis targeted therapy of classical Hodgkin lymphoma (cHL) according to genetically driven PD-L1 and programmed cell death ligand 2 (PD-L2) expression. Methods Five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Finally, deciphering how PD-L1 reverse signaling and CD30 signaling may influence the chromatin remodeling, and vice versa . Chen and coworkers recently indicated the high efficacy of anti- PD-1 treatment after failure of anti- PD-L1 therapy in relapsed/refractory HL, although the patient group in this study was of limited size ( 35 ). Moreover, a multicenter phase 1-2 clinical study, iMATIX, revealed the limited efficacy of the anti-PD-L1 inhibitor atezolizumab in HL treatment ( 159 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, deciphering how PD-L1 reverse signaling and CD30 signaling may influence the chromatin remodeling, and vice versa . Chen and coworkers recently indicated the high efficacy of anti- PD-1 treatment after failure of anti- PD-L1 therapy in relapsed/refractory HL, although the patient group in this study was of limited size ( 35 ). Moreover, a multicenter phase 1-2 clinical study, iMATIX, revealed the limited efficacy of the anti-PD-L1 inhibitor atezolizumab in HL treatment ( 159 ).…”
Section: Discussionmentioning
confidence: 84%
“…Tonsils, placenta, dendritic cells, monocytes in the liver and lungs are the only normal tissues that express PD-L1 ( 33 ). A unique feature of HRS cells is increased expression of PD-L1 and PD-L2 ( 34 , 35 ).…”
Section: Main Molecular Signaling Pathways In Hlmentioning
confidence: 99%
“…In addition, PD-1 inhibitor treatment, which inhibits both PD-1−PD-L1 and PD-1−PD-L2 interactions, has shown improved therapeutic efficacy in patients with relapsed or refractory Hodgkin lymphomas. 60 These results highlight the need to inhibit not only PD-1−PD-L1 but also PD-1−PD-L2 interactions and suggest that isolated hPD-1 variants that can inhibit both interactions may have greater therapeutic efficacy than hPD-1 variants that can only inhibit the PD-1−PD-L1 interaction.…”
Section: ■ Discussionmentioning
confidence: 80%
“…Besides PD-1 blockade, targeting PD-L1 is an alternative strategy to avoid PD-1/ PD-L1 immune checkpoints. However, it should be noted that PD-L1 and PD-L2, the two ligands to PD-1, are differentially expressed in the tumor microenvironment of cHL [29,99]. Therefore, anti-PD-L1 monotherapy may be not sufficient to completely inhibit the PD-1 pathway, its efficacy may be lower than PD-1 inhibition alone.…”
Section: Anti-pd-l1 Checkpoint Inhibitorsmentioning
confidence: 99%